Cybersecurity technologies for electronic education record (EER) systems based on blockchain and cloud computing - Kyrychenko, O.; Shmatko, O. V.; Кириченко, О.; Шматко, О. В. (ГО «Міжнародний центр наукових досліджень», 2025)
Traditional electronic education record (EER) management systems operate as isolated silos in which each educational institution maintains its own records independently. This separation complicates the verification and sharing of academic information across different platforms. Blockchain technology has recently emerged as a promising solution for secure and transparent record sharing among institutions operating on diverse infrastructures. However, storing complete education records directly on a blockchain remains impractical due to inherent storage limitations and the associated computational cost. To mitigate these challenges, this paper proposes a cloud-assisted blockchain model that combines the immutability of blockchain with the scalability of cloud storage. In the proposed architecture, blockchain technology ensures data integrity and access control through immutable transaction logs, while cloud computing provides an efficient and flexible medium for storing encrypted educational records. Elliptic Curve Cryptography (ECC) is employed to enable secure communication and mutual authentication among entities. The system has been validated through informal and formal methods, including AVISPA simulation and BAN logic analysis, demonstrating resistance to common cyber threats and confirming mutual authentication. Comparative evaluation indicates that the proposed model offers a practical balance between security, scalability, and efficiency, making it suitable for real-world academic environments.